The Innovative Roles of Entrepreneurial Catalyst to the Growth of New Ventures in Nigeria: A Case Study of the Center for Enterprise Development and Action Research - James, Aruleba Tomisin; Oluronke, Gbadegesin Omolara (Covenant Journal of Entrepreneurship, 2020)
The study focuses only on the micro and small enterprise development which is in alignment with the conference’s sub-themes. The study provides an avenue to explore the efforts of CEDAR in the growth of new ventures in Nigeria. Entrepreneurship, innovation and business growth have received scholarly attention over the years and have gone through many panels of discussions. Through this paper, a deeper investigation was made to identify the Innovative Roles of Entrepreneurial Catalyst to the Growth of New Ventures in Nigeria. The study specifically sought to; know how CEDAR has been able to help new enterprises to sprout up; ascertain the strategies being used by the CEDAR to grow the new ventures, via her micro and small enterprise development and micro-financing programmes. It is qualitative by making use of a semi-structured instrument (Aruleba, Olanipekun, Ayodele, & Adeagbo, 2019; Flanagan, Greenfield, Coad, & Neilson, 2015) as this would allow for the free flow of the respondentsâ€™ feelings, views and avoid manipulation. The qualitative study adopted a non-probability judgmental sampling technique to ascertain the key informants for the collection of soft data (recorded interview). The study concluded that new enterprises have been put up and supported to be birthed by various strategies employed by the CEDAR, since her inception in 1996. It, therefore, recommended that social organizations/enterprises and other non-profit making organizations should look inwardly in their various environment, in other to fill the gap that CEDAR has been filling across Africa.